Developing a fuzzy TOPSIS model in multiple attribute group decision making - Anisseh, Mohammad; Mohd Yusuff, Rosnah (Academic Journals, 2011)
Decision making is explained as a process through which, the solution for a problem is selected. Lack of perfect information evidently leads to uncertainty. Decision makers' opinion are expressed through words of natural language through a process of fuzzy multi attribute group decision making problem and aggregates the performance rating with respect to all the attributes for each alternative. In this paper, a technique for order preference by similarity to ideal solution (TOPSIS) has been dealt with in the fuzzy environment based on decision makers' viewpoint weights. The decision makers' fuzzy decision matrixes were converted into an aggregated decision matrix to determine the most preferable choice among all possible alternatives. Finally, a numerical example was used to illustrate the procedure of the method and compare it with other extant methods.